Evaluation of the Results of Fixation of Femoral Shaft Non-union with Implant failure by Ilizarov External Fixator Method (Journal of Dhaka National Medical College & Hospital, 2023)
Background: The Ilizarov operation is a type of external fixation procedure used in orthopedic surgery to lengthen or reshape limb bones as a limb-sparing technique to treat complex and/or open bone fracture, and in cases ofinfected non-union bones that are not amendable with other techniques. It is named after the orthopedic surgeon Gavriil Abramovich Ilizarov from the Soviet Union, who pioneered the technique.Objective: To find out the effectiveness of Ilizarov external fixator for implant failure and non-union of femoral shaft fracture with implant failure.Method: This prospective study of Evaluation of the result of fixation of femoral shaft non-union with implant failure by Ilizarov External fixator was carried out during the period of January 2019 to December 2021 atDepartment of Orthopedic Surgery in Dhaka National Medical College and Hospital, Dhaka. In total 10 patients with femoral shaft fracture non-union were selected as the study population. Mean age of the patients was 40 years. Majority of the patients were male. Among 10 cases 8 were found injury was high energy trauma due to motor vehicle accident and there was a preponderance of fracture on the right side. Removal of previous implant refer shinning of fracture ends, reduction and fixation under C-Arm.Result: In our study total 10 participants 8 male (80%) and 2 female (20%). So, male dominance was observed in this study. We found the highest 5 participants had injury from road accidents, 3 Sports injuries and rest only 2 from general falls. There is no intra-operative complication. As for the post-operative complications local pain with motion and local edema were seen in 4 cases, and painful tenting of skin in 6 cases. Delayed complications included Pin tract infection in 3 patients, restricted knee motion and shortening of limb 2 patients, Superficial wound infection 2 cases. Deep wound infection and Delayed union 1 patients. In this study results, 7 patients (70%) were excellent, 2 patients (20%) were good' I patient was fair.Conclusion: The present study we found some good features of using Ilizarov induced method in the treatment of femoral shaft non-union facture with implant failure.J. Dhaka National Med. Coll. Hos. 2023; 29 (01): 41-44